Chemical-Petrographic Types and Shock Metamorphism of 184 Grove Mountains Equilibrated Ordinary Chondrites - Deqiu Dai; Shuang Liu; Xuemei Liu (Minerals, 2018)
We reported the petrography and mineral chemistry of 184 equilibrated ordinary chondrites collected from Grove Mountains, Antarctica. The chemical-petrographic types and shock metamorphism degrees of these chondrites were assigned. They were classified into 46 H groups (22 H4, 20 H5, and four H6), 133 L groups (eight L4, 75 L5, and 50 L6), and five LL groups (four LL4 and one LL5). Some of these chondrites could be paired; however, both H and L group meteorites were affected. Further studies such as terrestrial ages and thermal luminescence are required in order to confirm the pairings. The relative abundances of H, L, and LL are different in Grove Mountain meteorites, when compared to those in Transcontinental Ridge meteorites. Based on the shock effects, the shock metamorphism degrees of these chondrites were assigned. Compared to previous studies, the heavily shocked samples of S4 and S5 have a higher fraction (59 out of 184) in Grove Mountain ordinary chondrites. The L group (54 out of 59) is the dominant chemical group in the heavily shocked chondrites, except for five meteorites which belong to the H group. The shock metamorphism degrees of the H and L groups are distinct, which may indicate different surface properties in their parent bodies. In addition, the petrologic types and shock degrees are probably closely related, with the most heavily shocked chondrites observed in types 5 and 6.